Mutagenic activity of cyclohexene and products of its chlorination - Sycheva, L. P.; Zholdakova, Z. I.; Polyakova, E. E.; Lukmanova, N. E.; Akhal'tseva, L. V.; Zhurkov, V. S. (Bulletin of experimental biology and medicine, 2000)
Cyclohexene exhibits no mutagenic effect in the Ames test. Products of its transformation (chlorination) produced a mutagenic effect in the Ames test on TA 100 strain without metabolic activation and in the micronucleus test on epithelial cells from mouse urinary bladder and colon. These findings are consistent with epidemiological data on higher incidence of urinary bladder and rectal cancers in subjects consuming chlorinated drinking water from surface water reservoirs.